A Brief Overview of Social Engineering: Muhammad Shairoze Malik - Malik, Muhammad Shairoze Malik (International Journal for Electronic Crime Investigation, 2020)
Abstract: Right now digitization, the requirement for information protection and information security is very significant. The IT organizations today lean toward their information over everything. Not just for organizations, information security is significant for any person. Be that as it may, regardless of how secure is the organization, how best in class is the technology utilized or what amount cutting-edge their product is, there’s as yet a weakness in each segment known as ’Human’. The craft of acquiring sensitive data from a person is known as Social Engineering. Technology has advanced rapidly in recent years, but the danger of Social Engineering still persists in the society. This is mostly due to lack of awareness regarding social engineering attack patterns. Social engineering is an extremely basic practice to accumulate data and touchy information using portable numbers, messages, SMS or direct methodology. Social engineering can be extremely valuable for the aggressor whenever done in an appropriate way. This paper will look into some of the basic and rudimentary techniques used by attackers to gain personal information about victims. The goal of the article is to enable others in successfully defending against social engineering attacks by having the knowledge into how these attacks are performed.